Institutional Investors and the Financialisation of Construction Companies in Poland: A Shareholder Value Approach - Oleksy, Paweł; Zyguła, Andrzej (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
The study examines how the presence of financial institutions in the ownership structure of non-financial corporations affects shareholder value. Based on the segmentation of shareholders (institutional and non-institutional investors), their impact on changes in the TSR and the MVA index was examined using logit models and panel data analysis. The analysis covers the years 2004–2014 and all the national construction companies listed on the Warsaw Stock Exchange at the end of 2014.The results confirm, particularly with respect to the MVA, that the presence of institutional investors in the shareholder structure increases the likelihood that the company will maximise shareholder value. It also revealed that institutional investors had a positive impact on this value criterion. This fact may be a symptom of financialisation in the construction sector.